2008
DOI: 10.1007/s10661-008-0656-0
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal levels in Prochilodus lineatus collected from the La Plata River, Argentina

Abstract: Most of the industrial, urban and sewage discharges are released into the La Plata River, Argentina without any previous treatment. However, few works have investigated the extent of metal contamination. The aim of this study was to assess the levels of cadmium, copper, lead and zinc in liver and gills of adults Prochilodus lineatus collected from three sampling stations along the coast of the La Plata River: Berazategui, Berisso and Atalaya (from north to south). Samplings were performed during 2002 and 2004.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Among these metals, Pb contributed most (32.4%) to the average HI of 40 TWTPs, followed by Cd (24.7%) and Cr (21.6%), which suggests that the three metals may be of serious health concerns for the local residents, since previous studies showed that Cr enrichment in the sediments of Yangtze River (Zhang et al 2009) and Huaihe River (Huang et al 2006) was widespread, and the sequence of the potential ecological risk posed by the metals in sediments of Yangtze River at Wanzhou Section was Cd > Pb > Cu > Zn > Cr (Fu et al 2009). These metals can be easily bio-accumulated in some fish species (Lombardi et al 2010;Malik et al 2010), so more concerns shoulds focus on the contamination of Pb, Cr and Cd in the source water in the region of Jiangsu.…”
Section: Non-carcinogenic Risk Induced By the Metalsmentioning
confidence: 99%
“…Among these metals, Pb contributed most (32.4%) to the average HI of 40 TWTPs, followed by Cd (24.7%) and Cr (21.6%), which suggests that the three metals may be of serious health concerns for the local residents, since previous studies showed that Cr enrichment in the sediments of Yangtze River (Zhang et al 2009) and Huaihe River (Huang et al 2006) was widespread, and the sequence of the potential ecological risk posed by the metals in sediments of Yangtze River at Wanzhou Section was Cd > Pb > Cu > Zn > Cr (Fu et al 2009). These metals can be easily bio-accumulated in some fish species (Lombardi et al 2010;Malik et al 2010), so more concerns shoulds focus on the contamination of Pb, Cr and Cd in the source water in the region of Jiangsu.…”
Section: Non-carcinogenic Risk Induced By the Metalsmentioning
confidence: 99%
“…The use of somatic indexes such as HSI, CF, and ∆K in environmental studies were considered useful tools to evaluate the influence of biotic factors in the accumulation of these types of contaminants (ADAMS; RYON, 1994;KARELS et al, 1998;COUILLARD et al, 1999;LOMBARDI et al, 2010). Azevedo et al (2009a) observed high HSI values in C. spixii from polluted sites in Santos-São Vicente estuary as compared with fish from a reference unpolluted area.…”
Section: Discussionmentioning
confidence: 99%
“…All biliary content was collect using a sterile syringe and stored at -20°C for subsequent analyses. Somatic indexes were calculated according with Vazoller (1996) and Lombardi et al (2010) The MFO system was measured in the microssomal fraction of the individual livers of C. spixi according with Livingstone (1988). Frozen livers (~1.00 g) were homogenized in buffer containing 10 mM Tris-HCl, 0.15 M KCl and 0.5 M sucrose (pH 7.6) and centrifuged three times: 500g for 15 min, 12,000g for 45 min and then at 100,000g for 90 min) Microssomal pellets were dissolved in 20 mM Tris-HCl and 20% glycerol (pH 7.6).…”
Section: Collection Of Animals and Sampling Sitesmentioning
confidence: 99%
“…The highest average concentration of copper was registered at the CP4 production center, at 0.0515 mg/L. The values above this concentration become toxic to fish and other aquatic organisms, even more so if they act synergistically with zinc (Lombardi et al, 2010;Sakulsak, 2012) (Table 5).…”
Section: Concentration Of Heavy Metals In Water Used For the Productimentioning
confidence: 99%